25k+3y+6k-11y=

Simple and best practice solution for 25k+3y+6k-11y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25k+3y+6k-11y= equation:


Simplifying
25k + 3y + 6k + -11y = 0

Reorder the terms:
25k + 6k + 3y + -11y = 0

Combine like terms: 25k + 6k = 31k
31k + 3y + -11y = 0

Combine like terms: 3y + -11y = -8y
31k + -8y = 0

Solving
31k + -8y = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '8y' to each side of the equation.
31k + -8y + 8y = 0 + 8y

Combine like terms: -8y + 8y = 0
31k + 0 = 0 + 8y
31k = 0 + 8y
Remove the zero:
31k = 8y

Divide each side by '31'.
k = 0.2580645161y

Simplifying
k = 0.2580645161y

See similar equations:

| -16n+9n+13n=-18 | | 4x+2x+2=10 | | 15a+6b-a+2b= | | 12(5x)=1 | | 3z^2-87z=-21 | | 28=8+0.4x | | 5g+25=115 | | 2s^2+92s=0 | | 6m-2p-3m+4p= | | 28=8+0.4 | | 10z+2.5x=156 | | 4u^2-21u+5=0 | | 288=8+0.4x | | 4x-10=x+20 | | -2(6-7n)+2=-94 | | 5z^2-12z-9=0 | | 6-4x=11x+3+7x | | 6p(-2p+5)=0 | | 3x-2-8=19 | | 7t-4t-2=13 | | a(3x+(-8))=b+(-18) | | 40u^2-250=0 | | -13+r=6r+8r | | 0.33333333333(v+100)=500 | | 19-g=15 | | -8x+-16=56 | | 6s+7=19 | | 0.25=1.5 | | (2x-5)=6(x-4)+9 | | Y=2.50x+2 | | 3rs+11s= | | x^2-80x+900=0 |

Equations solver categories